Implementing information literacy programs in Romanian Medical School - Still a Major Challenge - Madge, Octavia-Luciana; Robu, Ioana (Qualitative and Quantitative Methods in Libraries, 2020)
Medical students in Romania do not benefit from a coherent and uniform training in the field of information literacy provided by the academic libraries. There are information literacy sessions taught by librarians at the beginning of the academic year but a small questionnaire-based survey conducted in Romanian medical academic libraries revealed there is no library involvement in the delivery of information literacy courses included in the curriculum, except for the information literacy course taught by the librarian to doctoral medical students in Cluj. Taking this course as a model, a national project has been designed, aiming to implement in other large medical schools modules of information literacy taught by librarians. This study analyses the situation in Romania and starting from the course taught in Cluj for medical doctoral students, proposes modules of information literacy for students from programmes at all levels in medical schools.